An investigation into the effectiveness of the Basic Education assistance Module (BEAM)in reducing dropout rate in Mberengwa District Primary Schools. - Chatikobo, Tafadzwa (Midlands State University, 2017)
A study to investigate the effectiveness of BEAM in reducing dropout rate was carried out in Mberengwa North Cluster. The sample size had five school heads ,ten school teachers, five School Development Committee Chairperson, ten Community Selection Committee (CSC) members and thirty OVCs at school, which were selected at five different schools. Thirty parents and thirty orphans and vulnerable children from the communities surrounding the school were also chosen for the study. Questionnaires were administered to the teachers and the school heads. Interviews were conducted on the rest of the research participants. The study found out that there is still a problem of drop out prevailing in Mberengwa district and the BEAM programme is failing to address the issue. The study established that BEAM is a school fees assistance programme only. It does not provide other necessities for the children to learn like food, transport and stationary. The selection criteria are also subjective in some instance because there are some pupils who are benefiting from the BEAM programme who are neither poor nor vulnerable. The study recommends that the BEAM programme should be an inclusive approach that should not only pay for school fees but also cater for the students needs especially the safety needs like food, good shelter, and clothing.